Impact of jhum cultivation on the agro-ecology of mountains and socio-economy of Tribal peoples - S.M. Rezaul Karim; Mashhor Mansor (2011)
Jhum cultivation, popularly known as slash and burn is the most prevalent form of cultivation in the hills of tropical Asian countries including Bangladesh. Jhuming involves cutting patches forests of the mountains in January to March, left on the hill slopes for one month for drying and burning of the dried plants. Small holes are made throughout the sloppy fields and seeds of different crops are sown in the holes in April. Crops are harvested in succession as they ripe between July to December. This study examines the impacts of jhum cultivation on the management of soil and water resources, biodiversity, forest productivity and socio-economic conditions of the jhum cultivators (tribal peoples). A vast area of land comes under jhum cultivation every year in tropical Asia. The jhum cultivation lead to decline of productivity by 50%, the yields are almost equal to the input values and the farmers are experienced food shortage of 2 to 6 months every year. The jhum farmers adopt new occupations to support their livings. An amount of 100 to 250 metric tons of topsoil per hectare are depleted per year due to jhum cultivation. The rotation cycle of fallowing has been reduced from 7-8 to 3-4 years especially in Bangladesh. The forest birds, arboreal mammals and plants were disturbed significantly and a few species are found in the second-growth habitats created by jhum cultivation. The reasons for this mountain degradation were identified as government policies in classifying jhum fallow lands as wastelands or degraded forest which made end of community ownership. Creation of reserve forests, nationalization of jhum land by the government and planned resettlement of plain land peoples into hills are also the reason for mountain degradation and as a consequence of which the jhumias are moving to the marginal lands.